REVIEW ON THERAPEUTIC MANAGEMENT OF PAIN IN ANIMALS - G. Srinivasan; U. Sunilchandra; N. B. Shridhar; Aruru Keerthana (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Animal pain management is an important aspect in veterinary medicine. Trauma, illness and surgery can all result in acute pain and good management of pain is required for animal welfare (i.e., Health, physical and mental wellbeing). Newer classes of drugs are emerging for the management of pain which has lesser side effects and more efficacy than older drugs which were used against pain. Combination of two or more drugs has been proved to be more effective for the management of pain than the single drug usage. Selection of the most suitable drug combination is based on the severity of pain, effectiveness of the drug and also health status of the animal. Management of animals that are under pain needs a combination of good nursing, nondrug therapies (for example, ice packs or heat, bandaging and physical therapy) and drug treatments. The article reviews about the classes of drugs which are used for the management of acute and chronic pain in animals, their most common side effects, and the treatment regimen for different class of drugs. It is aimed to guide the veterinary practitioner to select and dose the animals with effective analgesics for the management of pain.